Konsep Soteriologi dalam Ritual Tungku Bokong di Kecamatan Reok Barat, Kabupaten Manggarai: Tinjauan Teologis dan Kultural - Yosef Gunawan (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
The Tungku Bokong ritual is a traditional practice of the Manggarai people found in Reok and West Reok Districts, Manggarai Regency. This study aims to analyze the soteriological concept within the ritual, focusing specifically on its implementation in West Reok District. The research employs a descriptive qualitative approach through in-depth interviews with customary leaders and a review of relevant literature. The findings reveal that Tungku Bokong literally means “reconnecting the provision (blessing),” referring to an effort to restore the flow of blessings believed to have been disrupted an interruption that is thought to cause life problems such as illness, misfortune, or nightmares. The uniqueness of this ritual lies in its understanding that suffering and life difficulties can become a gateway to blessings or restoration. The central questions guiding this research are how the Tungku Bokong ritual is regarded as an act of attaining salvation for an individual, and what meaning it holds for the people of West Reok District. The study shows that the salvation gained through this ritual is not only material but also involves the restoration of relationships with ancestors and the Creator (Mori Kraeng). Meanwhile, suffering and various life challenges are understood as consequences of a disrupted blessing and as a means of awakening individuals to return to a balanced life.